Marketing Strategy of an event management firm- a case study done on I-Alo events and marketing Ltd - Porshi, Mehjabin (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.